Divje babe I Paleolitsko najdišče mlajšega pleistocena v Sloveniji (2. del: Arheologija) = Upper Pleistocene Palaeolithic site in Slovenia (Part 2: Archaeology) - Turk, Ivan (Opera Instituti Archaeologici Sloveniae, 2014)
The second part of the monograph on Divje babe I deals in detail with archaeological finds from this important Middle and Upper Palaeolithic site. Edited by Ivan Turk, the monograph contains 17 chapters, written by seven authors.